Influencer Contributions, Hedonic Browsing and Visual Appeal Against Impulsive Buying Online Shopping Customers - Mai Hetti, Selvi; Iskandar, Dedi; Ruri Aditya Sari (SEAN Institute, 2024)
This research aims to measure the contribution and influence of influencers, hedonic browsing, and visual appeal on impulsive buying behavior among online shopping customers. Tight competition in e-commerce in Indonesia, especially on platforms such as Shopee and Instagram, encourages various marketing strategies to increase sales. One strategy is to use influencers who can influence consumers' impulse purchasing decisions. This research uses quantitative methods by collecting data through questionnaires distributed to 65 respondents who are Shopee and Instagram users. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3 software. The research results show that influencers contribute 20.5% to impulsive buying, hedonic browsing contributes 57.5%, and visual appeal contributes 79%. % of hedonic browsing. These findings provide important implications for retailers in determining effective marketing strategies to encourage impulse buying behavior, with an emphasis on the use of influencers and increasing the visual appeal of online shopping platforms. This research also provides insight into the development of marketing science, especially in the context of e-commerce